The Effect of Soybean Pulp Planting Media Use on the Growth and Production of Lettuce Plants (Lactuca Sativa L.) - Ahmad Mauludin Zakaria; Agus Miftakhurrohmat (Universitas Muhammadiyah Sidoarjo, 2016)
This study aims to determine the effect of the use of tofu dregs growing media on the growth and production of lettuce (Lactuca sativa L.). The study was conducted in July 2015 to September 2015 on polybag land in Kedung Peluk Village, Candi District, Sidoarjo Regency. This place is 20 m above sea level. A single factor experiment was arranged in a Randomized Block Design with 10 levels of combination treatment between soybean pulp and soil consisting of A1 = 0% soybean pulp and 100% soil, A2 = 10% soybean pulp and 90% soil, A3 = 15% soybean pulp and 85% soil, A4 = 20% soybean pulp and 80% soil, A5 = 25% soybean pulp and 75% soil, A6 = 30% soybean pulp and 70% soil, A7 = 35% soybean pulp and 65% soil, A8 = 40% soybean pulp and 60% soil, A9 = 45% soybean pulp and 55% soil, A10 = 50% soybean pulp and 50% soil. From the ten treatments, it was repeated 3 times and obtained 30 units of trials. The results showed that the treatment of using soybean pulp media with a combination of 20% soy- bean pulp and 80% soil gave the best response to lettuce plant growth, namely on plant height, leaf width, number of leaves, root length, wet weight of the upper part of the plant and total weight.